A antinocicepção induzida pela ingestão de óleo - resina de copaíba (Copaifera langsdorffii) nanoencapsulado recruta receptores opioides µ1 e Κ da substância cinzenta periaquedutal ventrolateral - Silva, Mariane Costa (2020)
Copaiba trees (Copaifera langsdorffii), also known as diesel trees, are native to Latin America and easily found in the Amazon rainforest region. The oil extracted from this tree is widely used by the general population due to its anti-inflammatory and healing properties. Several studies report that copaiba oil has anti-inflammatory, antiseptic, antimicrobial properties, and promotes antinociception. The use of drugs in the nanostructured form has numerous advantages when compared to unitary systems, such as controlling the release of the drug, selective distribution of active substances, increasing its therapeutic indexes, optimizing the speed of release and dosing system of the substances, and reducing the risk of toxicity. Some studies show that copaiba oil in nanostructured form presents better results than when compared to its free form. From the evidence found by Reynods in 1969, showing that by electrically stimulating the periaqueductal grey substance (SCP) it was possible to induce a potent analgesia, several studies were started to understand how structures involved in this endogenous pain inhibition system work. The SCP corresponds to a thick grey layer that surrounds the cerebral aqueduct, running longitudinally across the midbrain. The presence of µ1 and κ types of opioid receptors in SCP seems to be involved in antinociceptive processes, since the administration of a nonspecific agonist for opioid receptors in this mesencephalic structure causes powerful analgesia. The antinociception promoted by the intake of copaiba oil also seems to be modulated by opioid mechanisms, as the administration of the nonspecific blocker of opioid receptors naloxone reverses this effect. This study aimed to investigate the analgesia promoted by ingesting nanostructured copaiba oil and the role of µ- and κ- opioid receptors in the ventrolateral column of the periaqueductal grey matter (SCPvl) in this antinociceptive process. We performed a doseresponse curve submitting laboratory animals to the tail-flick test to verify the analgesic effects promoted by the nanostructured copaiba oil. We assessed the pharmacological activity of the opioid receptors in the midbrain through the microinjection of specific opioid receptors antagonists, nor-Binaltorfimina and Naloxonazine, in SCPvl, with nociceptive thresholds measured after drug pretreatment. Nanosystems were developed by nanoprecipitation method and characterised as the average particle diameter, zeta potential and pH. Our results indicated that the nanostructured copaiba oil, in a dose of 2 mg / kg, was the most effective, as there was a significant increase in antinociception compared to the control. Morphine administered intraperitoneally at 1 mg / kg caused an increased latency of tail flick latencies at all times tested, and comparing to the group of animals that received nanostructured copaiba oil (2 mg / kg), there was no statistically significant difference, suggesting that copaiba oil has an antinociceptive effect similar to that of morphine. Microinjections of μ and κ opioid receptors selective antagonists in the SCPvl impaired antinociception promoted by the intake of nanostructured copaiba oil, suggesting that, at least part of this antinociceptive process is due to the recruitment of μ1- and κ opioid receptors of the SCPvl.